PENGETAHUAN LOKAL MASYARAKAT TEMANGGUNG DALAM BASA TEMANGGUNGAN (SEBUAH TELISIK ETNOLINGUISTIK) - Muanayah, Nur Alfi; Sabela, Raudina Sabela; Fitrianti, Syalma Indah (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2023)
This study aims to use an ethnolinguistic viewpoint and a phenomenological approach to explain the meaning of linguistic units in the Javanese Temanggung dialect. This is in line with the theory of language relativity put forward by Humbolt thesis of language relativity, which claims that there is a link between society, language, and culture, and that each language includes a unique world view. The core data in this study are the linguistic expressions in Basa Temanggungan video, and the secondary data are key informant confirmation and verification results regarding the meaning of lingual units found in the video.The findings suggest that language expressions can describe people's local knowledge based on their culture. The term usel, for example, refers to donated money that is wrapped in a little envelope and given to the host when attending a celebration. It is termed usel because it is offered to the host by slipping it into the host’s hand. The habit of small chat is still very prominent in Javanese society, the host receives the donation with small conversation as if he were about to decline it, forcing the giver to push the host to accept it by tucking it in. The word usel is only used by Temanggung people, not by individuals from other communities.